Cytokine Networks Dysregulation during HTLV-1 Infection and Associated Diseases - Futsch, Nicolas (Viruses, 2018)
Human T-cell leukemia virus type 1 (HTLV-1) is the causative agent of a neural chronic inflammation, called HTLV-1-associated myelopathy/tropical spastic paraparesis (HAM/TSP) and of a malignant lymphoproliferation, called the adult T-cell leukemia/lymphoma (ATLL). The mechanisms through which the HTLV-1 induces these diseases are still unclear, but they might rely on immune alterations. HAM/TSP is associated with an impaired production of pro-inflammatory cytokines and chemokines, such as IFN-γ, TNF-α, CXCL9, or CXCL10. ATLL is associated with high levels of IL-10 and TGF-β. These immunosuppressive cytokines could promote a protumoral micro-environment. Moreover, HTLV-1 infection impairs the IFN-I production and signaling, and favors the IL-2, IL-4, and IL-6 expression. This contributes both to immune escape and to infected cells proliferation. Here, we review the landscape of cytokine dysregulations induced by HTLV-1 infection and the role of these cytokines in the HTLV-1-associated diseases progression.